Asuhan Keperawatan Pada Ny. M dengan Post Amputasi Ulkus Diabetik Digiti Dekstra II, III, IV dan V Hari Ke-7 di Ruang Cempaka Rumah Sakit Umum Daerah Pandanarang Boyolali - Kusuma, Danang Arvina Cahya; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2013)
Background: Amputation of diabetic ulcers is a management to prevent sepsis. Amputation often occurs patient with diabetes who had width injury, commonly in lower extremity Goals: To know description of nursing care in patients with post amputation of diabetic ulcers involve assesment, intervention, implementation, and nursing evaluation. Result: After compare between nursing care in General Regional Hospital Of Pandanarang Boyolali and theory from book mannual have result there are diagnosis in the case same with book mannual and is'nt same with theory. In addition writer see diagnosis have must to didn't appear in the case because not appropiate with theory. Conclusion: people with diabetes melitus must be give save enviroment from injury with the result that keep from diabetik ulcers. Principal treatment on the people with diabetik ulcers is wound care specifically for diabetik ulcers, because with precision wound care diabetik ulcers can be save from amputation. In other words the priority treatment for people who had amputation is wound care post amputation in order to save from repeated amputation.